Evaluation of Domestic and Institutional Plastic Waste Generation and Management in Awka South Local Government Area of Anambra State - Udebuani, O. F.; Nnodu, V. C. (International Journal of Real Estate, 2025)
The research objectives were to evaluate the quantity and composition of plastic waste, identify its sources and causes, examine current management practices, evaluate environmental impacts, and propose sustainable strategies for improvement. Data were collected through structured questionnaires distributed to households, schools, and hospitals within Ifite, Okpuno, and Agu Awka (GRA) over six months (June–November 2024). The study found that both households and institutions generate significant amounts of plastic waste daily, with institutions (schools and hospitals) producing higher quantities (56.45%). Packaged food and beverage plastics (24.07%) were the most common waste category. Analysis of current waste management practices revealed that burning (49.39%), open dumping (41.66%), and burying (45.06%) were the predominant methods, highlighting ineffective waste management. The study concludes that ineffective plastic waste management contributes to environmental pollution and health hazards. Sustainable strategies, such as policy enforcement, incentives for waste reduction, private-sector collaboration, and investment in recycling technologies, are recommended to improve plastic waste management in Awka South LGA. These findings provide a framework for policymakers and stakeholders to implement effective plastic waste management solutions.
Keywords: Plastic waste; domestic waste; institutional waste; management practices